Bioactivators and nitrogen fertilization applied to durum wheat: effects on the chemical composition and in vitro digestibility of straw - De Giorgio D.; Lestingi A.; Bovera F.; Convertini G. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
The objective of this research was to study the effects of three nitrogen fertilisation levels and bio-activators on the chemical composition and dry and organic matter digestibilities of durum wheat straw. The following applications of bio-activators were compared; mycorrhizal, Azospirillum and mycorrhizal plus Azospirillum inoculation and in addition a control with no application. These treatments were in factorial combination with three levels of N fertilization (0, 50, 100 kg/ha of N). The following parameters were determined: dry matter, crude protein, ether extract, ash, neutral detergent fibre, acid detergent fibre and acid detergent lignin. Hemicellulose and cellulose were estimated. The highest dose of nitrogen fertilizer increased neutral and acid detergent fibre and cellulose straw percentages. The two bio-activators had different effects on the quality of the straw: the mycorrhizal bio-activator increased neutral and acid detergent fibre and the cellulose contents of the straw, the Azospirillum also showed an increase in the same parameters. Neither treatment affected dry and organic matter digestibilities. The results of this research show that high levels of nitrogen can have a negative effect on the quality of straw and it is therefore recommended that a quantity of 50 kg/ha of N be used. Mycorrhizal, even in small doses, reduced fibre and increased cellulose content.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)